A Perturbed Asymmetrical Y-TypeSheathless Chip for Particle Control Based on Adjustable Tilted-Angle Traveling Surface Acoustic Waves (ataTSAWs) - Junping Duan; Miaomiao Ji; Binzhen Zhang (Biosensors, 2022)
The precise control of target particles (20 µm) at different inclination angles θi is achieved by combining a perturbed asymmetric sheathless Y-type microchannel and a digital transducer (IDT). The offset single-row micropillar array with the buffer area can not only concentrate large and small particles in a fixed region of the flow channel, but also avoid the large deflection of some small particles at the end of the array. The addition of the buffer area can effectively improve the separation purity of the chip. By exploring the manufacturing process of the microchannel substrate, an adjustable tilted-angle scheme is proposed. The use of ataTSAW makes the acoustic field area in the microchannel have no corner effect region. Through experiments, when the signal source frequency was 33.6 MHz, and the flow rate was 20 µL/min, our designed chip could capture 20 µm particles when θi = 5°. The deflection of 20 µm particles can be realized when θi = 15°–45°. The precise dynamic separation of 20 µm particles can be achieved when θi = 25°–45°, and the separation purity and efficiency were 97% and 100%, respectively.